Penerimaan Diri Perempuan Korban Sekstorsi: Sebuah Tinjauan Literatur Naratif - Adhita Putri Ariani; Herdiana, Ike (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
Sextortion is a term that has recently emerged from the word's "sex" and "extortion". Sextortion involves the distribution of sexual images of victims as a threat to obtain money or other valuables. Victims of sextortion have experienced a traumatizing experience that requires a long process of self-acceptance of their situation. This study was obtained from articles related to the problem and aimed to analyze the self-acceptance process of sextortion victims after the incident as well as the factors involved in the victims' self-acceptance process. This study found that the self-acceptance process of post-incident sextortion victims has several stages, starting from the denial phase, self-evaluation, self-awareness, and self-acceptance phase. The factors that influence the self-acceptance process were divided into two, namely internal factors in the form of self-understanding, self-awareness and self-will to change the situation and external factors, namely the environment around the victim.